2016
DOI: 10.1103/physrevb.94.235413
|View full text |Cite
|
Sign up to set email alerts
|

Quantum transport in graphene Hall bars: Effects of vacancy disorder

Abstract: Using the tight-binding model, we investigate the influence of vacancy disorder on electrical transport in graphene Hall bars in the presence of quantizing magnetic fields. Disorder, induced by a random distribution of monovacancies, breaks the graphene sublattice symmetry and creates states localized on the vacancies. These states are observable in the bend resistance, as well as in the total DOS. Their energy is proportional to the square root of the magnetic field, while their localization length is proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The fabrication of GNC on HMDS allows for a better definition of the edges while overcoming some of the limitations that occur in processing encapsulated graphene. Also, we cannot rule out a higher concentration of vacancies in the GNCs fabricated on heterostructures of graphene and hBN due to the transfer technique reported in Ref. .…”
Section: Electron Transport Resultsmentioning
confidence: 92%
“…The fabrication of GNC on HMDS allows for a better definition of the edges while overcoming some of the limitations that occur in processing encapsulated graphene. Also, we cannot rule out a higher concentration of vacancies in the GNCs fabricated on heterostructures of graphene and hBN due to the transfer technique reported in Ref. .…”
Section: Electron Transport Resultsmentioning
confidence: 92%
“…It has been found that divacancies can affect the mechanical [12,13,14,15], electrical [16,17,18], magnetic [19,20] and chemical [21,22] properties of graphene. Some of these effects can provide some useful performance qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field in the quantum model is implemented through Peierls phase, as explained in Ref. 22, and the resistances are obtained by applying the Landauer-Büttiker formalism for a four-terminal 23 and multi-terminal 24 device.…”
Section: Focusing System and Sgm Potentialmentioning
confidence: 99%